Pendampingan Pelaku UMKM dalam Penerbitan Nomor Induk Berusaha (NIB) dan Sertifikasi Pemenuhan Komitmen Produksi Pangan Olahan Industri Rumah Tangga (SPP IRT) di Desa Ponggang, Kecamatan Serangpanjang, Kabupaten Subang - Hardiyanto Rahman (Civitas Consecratio: Journal of Community Service and Empowerment, 2023)
The Ease of accessing the issuance of Business Identification Numbers (NIB) and Certification of Fulfillment of Commitments for Processed Food Production for the Home Industry (SPP IRT) is apparently not widely known by the public, especially UMKM business actors, there is still a public perception that the issuance of these documents requires many conditions and requires for a long time, so that many business actors do not yet have the legal documents. Of course, it is different from the current policy that accessing these documents is very easy and does not require a long time. This community service activity aims to provide socialization to the community, village officials, business actors, BUMDes that the process for issuing IRT NIB and SPP is very easy, preparing the required documents for issuing IRT NIB and SPP, and assisting in the issuance of IRT NIB and SPP. This activity method is carried out through lectures, training and practice regarding OSS, NIB and SPP IRT policies. The result of this community service is that the implementation of the socialization went well with high interest from business actors to be able to issue NIB and SPP IRT which was marked by the publication of 6 (six) NIB and 3 (three) SPP IRT Ponggang Village business actors. Furthermore, it is hoped that business actors can prepare themselves within 3 (three) months from the issuance of the SPP IRT to fulfill commitments and the Village Government can assist the community in the preparation process, and it is also hoped that the Ponggang village government can continue to improve their knowledge and skills so that this activity can keep going.